2007
DOI: 10.1080/12265080701561984
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Specialization and New Determinants of FDI: Evidence from South and East Asia

Abstract: By estimating a dynamic panel-gravity model of bilateral foreign direcr investment (FDI), this article investigates the location determinants of inward FDI in South and East Asia and assesses their short-run and long-run effects. The econometric results highlight the importance of the vertical specialization-, trade-, and international integration-related location factors. The gravity-specific variables are also found to be significant location determinants, whilst some of the traditional determinants are foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…The increases in trade and deeper relations with many Sub-Saharan African countries have naturally made investment in the region both easier and more desirable. This is collaborated by the findings of Vogiatzoglou (2007), who finds that bilateral trade and vertical specialization links between the recipient and host countries are important determinants for drawing FDI. This explains the recent rise in Chinese investment in the African continent and also suggests that these flows will continue to increase as the two regions draw closer in the future.…”
Section: African Growth and Chinese Fdisupporting
confidence: 76%
“…The increases in trade and deeper relations with many Sub-Saharan African countries have naturally made investment in the region both easier and more desirable. This is collaborated by the findings of Vogiatzoglou (2007), who finds that bilateral trade and vertical specialization links between the recipient and host countries are important determinants for drawing FDI. This explains the recent rise in Chinese investment in the African continent and also suggests that these flows will continue to increase as the two regions draw closer in the future.…”
Section: African Growth and Chinese Fdisupporting
confidence: 76%
“…Agosin and Machado (2007) developed an ordinal index in order to measure the openness of FDI policy regimes in developing countries and found that openness is a factor that permits FDI. A later study by Vogiatzoglou (2007), who investigated the location determinants of inward FDI in South and East Asia, found that if the degree of integration of the host country to the international economy rises, inward FDI also increases in the long run. Trade openness, therefore, has a significantly positive effect on FDI.…”
Section: Macroeconomic Fundamentalsmentioning
confidence: 97%
“…Blonigen and Wang (2004) argue that the factors determining the location of FDI vary systematically across LDCs and DCs in a way that is not captured by the current empirical models of FDI. Although some authors, including Chantasasawat et al (2010), Plummer andCheong (2009), andVogiatzoglou (2007), have examined the determinants of FDI in East and Southeast Asian countries, these studies analyzed Asian host countries with dissimilar characteristics, such as major FDI-seeking countries (including Indonesia and Thailand) as well as major FDI-making countries (like the Republic of Korea, Malaysia, and Singapore). Nonetheless, SAFTA countries were not in the sample.…”
Section: Literature On Fdi Determinantsmentioning
confidence: 99%
“…Along with numerous applications of the gravity model in empirical studies of international economics, authors including Anderson (1979), Bergstrand (1985Bergstrand ( , 1989, Deardorff (1998), Evenett and Keller (2002), and Feenstra et al (2001) have provided theoretical justification for the model. Recent empirics based on sound theoretical foundations have led to a richer and more accurate estimation and interpretation of the spatial relations described by the gravity model (Anderson 2011 Bevan and Estrin (2004), Busse et al (2010), Dee and Gali (2003), Gast and Herrmann (2008), Lee and Plummer (2004), Lesher and Miroudot (2006), Vogiatzoglou (2007), and Wei (2000) have applied the gravity model to investigate FDI determinants. In line with Newton's Law of Gravitation, the econometric model (1) outlines the core form of the gravity model of panel data ln(FDI ij t ) = C + β 1 ln(GDP it ) + β 2 ln(GDP jt ) + β 3 ln(GDPPC it ) + β 4 ln(GDPPC jt ) + β 5 ln(DIST ij ) + ε ij t .…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation